Accuracy control of contour milling on CNC machines - Y. Petrakov; D. Shuplietsov (Mechanics and Advanced Technologies, 2018)
The possibility of checking the accuracy of contours directly on a CNC machine equipped with a three-axis contact probe is proved. The technique of accuracy control of parts contours is presented, which is based on three-coordinate contact probe measurements according to the developed control program using standard CNC commands with automatic data entry into the file. The created application program performs the demonstration and visualization of the results. The application program loads the milling control program in the form of G-codes and a measurement data file, and all the necessary results for the accuracy evaluation appear in the graphics window